Best Answer

x=5.5

4x+1= 2x+12

-1 -1

4x=2x+11

-2x -2x

2x=11

/2 /2

x=5.5

Q: What is 4x plus 1 equals 2x plus 12 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

4x + 6 = 6x - 12-4x -4x6 = 2x - 12+12 +1218 = 2xx=9

2x + 5 = 7 - 4x ie 2x + 4x = 7 - 5 ie 6x = 2 x = one third.

In standard form, -6 + y = 2x is 2x - y + 6 = 02y - 4x = 12 is 4x - 2y + 12 = 0Each coefficient of the second is twice the corresponding coefficient of the first. So the equations are the same (and therefore dependent).In standard form, -6 + y = 2x is 2x - y + 6 = 02y - 4x = 12 is 4x - 2y + 12 = 0Each coefficient of the second is twice the corresponding coefficient of the first. So the equations are the same (and therefore dependent).In standard form, -6 + y = 2x is 2x - y + 6 = 02y - 4x = 12 is 4x - 2y + 12 = 0Each coefficient of the second is twice the corresponding coefficient of the first. So the equations are the same (and therefore dependent).In standard form, -6 + y = 2x is 2x - y + 6 = 02y - 4x = 12 is 4x - 2y + 12 = 0Each coefficient of the second is twice the corresponding coefficient of the first. So the equations are the same (and therefore dependent).

x=5. 10x-4x (6x) +10-6x (=10) If 10 is 2x, x=5.

8x+30=4x+18 -4x -4x 4x+30=18 -30 -30 4x=-12 4x/4=-12/4 x=-3

Related questions

4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3

2x-3=4x+9 -2x-12=0 2x=-12 x=-6

-2x = -4x + 24 -2x + 4x = 24 2x = 24 x = 24/2 x = 12

4x - 7 = 2x + 5 2x - 7 = 5 2x = 12 x = 6.

4x + 12 = 2x - 2Subtract 2x from each side:2x + 12 = -2Subtract 12 from each side:2x = -14Divide each side by 2:x = -7

4x + 6 = 6x - 12-4x -4x6 = 2x - 12+12 +1218 = 2xx=9

4x - 5 + 2x = 37

They are parallel lines.

2x + 6x + 4x = 12x

-2x=-4x*24 x=12

-2x = -4x + 24 2x = 24 x = 12

4x - 7 = 2x + 15 4x = 2x +222x = 22x = 11